2004
DOI: 10.1038/sj.tpj.6500283
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic variability of ERCC2 polymorphisms

Abstract: Excision Repair Cross-Complementing Rodent Repair Group 2 (ERCC2) plays an important role in DNA repair by eliminating bulky DNA adducts produced by platinum agents during the nucleotide excision repair pathway. Several studies have associated polymorphisms in ERCC2 with response to platinum therapy, lung cancer risk, and DNA repair capacity. This study examined ERCC2 polymorphisms and haplotype structure across 18.9 kb in 95 European, 95 African, and 95 Asian individuals. Single-nucleotide polymorphisms (SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, the haplotype structure and frequency between populations were significant different in European, African and Asian individuals. In both the African and Asian populations, C156A was not significantly linked to A751C [73] . In our meta-analysis, the 156A allele frequency was varied from0.441 to 0.459 in Asian and very different from African Americans (0.136).…”
Section: Discussionmentioning
confidence: 59%
“…However, the haplotype structure and frequency between populations were significant different in European, African and Asian individuals. In both the African and Asian populations, C156A was not significantly linked to A751C [73] . In our meta-analysis, the 156A allele frequency was varied from0.441 to 0.459 in Asian and very different from African Americans (0.136).…”
Section: Discussionmentioning
confidence: 59%
“…In our previous research on a Chinese lung cancer study group (Yin et al 2006), ERCC2 Lys751Gln and Arg156Arg were at incomplete linkage disequilibrium at a relatively lower level (D 0 = 0.355). A study (King et al 2005) found that ERCC2 codon 156 was linked to codon 751 in a European population, but not in African and Asian populations (D 0 values were not significant). Their findings agree with ours.…”
Section: Discussionmentioning
confidence: 85%
“…The linkage between Lys751Gln and Asp312Asn was r 2 = 0.56 in populations of European ancestry and r 2 = 0.11 in populations of African ancestry [19]. Therefore, linkage disequilibrium differences among these populations may also impact on the outcomes of these polymorphisms [60].…”
Section: Discussionmentioning
confidence: 97%